Scale for maternity role perceptions - ALPAR, ŞULE; BİLGİN, ZÜMRÜT (TAYLOR & FRANCIS INC, 2021)
The purpose of this study was to develop and test the psychometric properties of the Maternal Role Perception Scale, a measure of motherhood, based on the perceptions of women. The 5-point Likert draft scale with 61 items was used. The data of 610 mothers were analyzed in the study. In the validity-reliability analysis of the scale, exploratory factor analysis and Cronbach's alpha coefficients were used. As a result of the factor analysis, the scale consists of 28 items and two factors explaining 55.741% of the total variance. The internal consistency coefficient (Cronbach's alpha) of the scale was calculated as 0.952. The Maternity Role Perception Scale (MRPS) is a reliable and valid scale developed for Turkish women. Maternal role is affected by physical, psychological, social status and the life of the woman. It is recommended to apply MRPS on different samples.
Keywords: ADJUSTMENT; COEFFICIENT; TRANSITION; SUPPORT; MOTHER; CARE